Motion of a charged particle in a constant and uniform electromagnetic field - Ladino Gaspar, Luis; Rondón Troncoso, Hermilda Susana; Orduz Camacho, Patricia (IOP Publishing Ltd, 2015)
This paper focuses on the use of software developed by the authors that allows the visualization of the motion of a charged particle under the influence of magnetic and electric fields in 3D, at a level suitable for introductory physics courses. The software offers the possibility of studying a great number of physical situations that can significantly facilitate students’ understanding of this topic.

Este trabajo se centra en el uso de un software desarrollado por los autores que permite visualizar el movimiento de una partícula cargada bajo la influencia de campos magnéticos y eléctricos en 3D, a un nivel adecuado para cursos introductorios de física. El software ofrece la posibilidad de estudiar un gran número de situaciones físicas que pueden facilitar significativamente la comprensión de este tema por parte de los estudiantes.